2018
DOI: 10.32677/ijch.2018.v05.i10.002
|View full text |Cite
|
Sign up to set email alerts
|

Recovery pattern in severely malnourished children fed with World Health Organization F-75 diet and homogenized toned milk

Abstract: Background: An average 8 million Indian children younger than 5 years (under-fives) are severely wasted. Each year approximately 2.3 million deaths among 6–60 months aged children in developing countries are associated with malnutrition, which is about 41% of the total deaths in this age group. Objective: The objective of the study was to compare the efficacy of cereal-based the World Health Organization (WHO) F-75 diet and homogenized toned milk with added sugar in the recovery of presenting complaints and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Another study also concluded that lactose burden in feed leads to low stool pH which is indicator of carbohydrates malabsorption and changing lactose to sucrose may facilitate absorption. Another study also indicates that lactose free formula in malnourished children with diarrhea results in significant reduction in diarrhea and linked directly to low osmolarity 12,13 . Present study concluded that patients who were taking sugar and lactose containing standard F75 feeds were observed to develop an increase in diarrhea and vomiting leading to dehydration during the initial phase of treatment and patients who were taking low sugar rice based F75 had lower risk of these complications.…”
Section: Resultsmentioning
confidence: 94%
“…Another study also concluded that lactose burden in feed leads to low stool pH which is indicator of carbohydrates malabsorption and changing lactose to sucrose may facilitate absorption. Another study also indicates that lactose free formula in malnourished children with diarrhea results in significant reduction in diarrhea and linked directly to low osmolarity 12,13 . Present study concluded that patients who were taking sugar and lactose containing standard F75 feeds were observed to develop an increase in diarrhea and vomiting leading to dehydration during the initial phase of treatment and patients who were taking low sugar rice based F75 had lower risk of these complications.…”
Section: Resultsmentioning
confidence: 94%
“…Due to the severe clinical condition of hospitalized children, ready therapeutic foods are prescribed in a planned manner. According to nutrition science, reductive adaptation, downregulation of metabolic‐dependent functions, is one of the causes of high energy density intolerance at the beginning of diet therapy in children [ 132 ]. Hence, initially F‐75 therapeutic milk is suggested for the relative stability of metabolic homeostasis, and then F‐100 or RUTF which have a similar formula base, are substituted to compensate for growth failures [ 131 ].…”
Section: Childhood Malnutrition Treatmentmentioning
confidence: 99%